Implementation Of Tax Incentive Policies Motorized Vehicles In Increasing Local Revenue Of Makassar City - Nurul Wahidah; H, Herman; Suarlin; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2025)
This research aims to identify and describe the process of implementing motor vehicle tax incentive policies in increasing local revenue in Makassar city along with supporting and inhibiting factors. Descriptive qualitative research type. Data collection techniques through observation, interviews and documentation. The data analysis technique includes data condensation, data presentation and conclusion drawing. The results showed that the implementation of the policy of providing motor vehicle tax incentives in increasing local revenue in the city of Makassar has not been carried out properly and has not gone according to theory. This can be seen from Edward III's theory which is used to see the successful implementation of tax incentive policies, showing that the indicator (1) communication has not run optimally. This can be seen from the distribution of communication related to the policy of providing motor vehicle tax incentives is still lacking, (2) resources, running optimally. This can be seen from the quality of the ability of staff who know their authority and good facilities so that they are very helpful in implementing the policy. (3) disposition, running optimally. This can be seen from the appointment of bureaucracy and incentives running according to the rules in force. (4) bureaucratic structure, running optimally. This can be seen from the clear fragmentation of the SOP in implementing the policy, as well as explaining the impact of the implementation of the tax incentive policy on local revenue.